Deterioration of Organ Function As a Hallmark in Sepsis: The Cellular Perspective - Bauer, Michael; Coldewey, Sina M.; Leitner, Margit; Löffler, Bettina; Weis, Sebastian; Wetzker, Reinhard (Frontiers in Immunology, 2018)
Development of organ dysfunction discriminates sepsis from uncomplicated infection. The paradigm shift implicated by the new sepsis-3 definition holds that initial impairment of any organ can pave the way for multiple organ dysfunction and death. Moreover, the role of the systemic inflammatory response, central element in previous sepsis definitions, has been questioned. Most strikingly, a so far largely underestimated defense mechanism of the host, i.e. “disease tolerance”, which aims at maintaining host vitality without reducing pathogen load, has gained increasing attention. Here we summarize evidence that a dysregulation of critical cellular signaling events, also in non-immune cells, might provide a conceptual framework for sepsis-induced dysfunction of parenchymal organs in the absence of significant cell death. We suggest that key signaling mediators, such as PI3K, mTOR and AMPK, control the balance of damage and repair processes and thus determine the fate of affected organs and ultimately the host. Therapeutic targeting of these multi-functional signaling mediators requires cell-, tissue-, or organ-specific approaches. These novel strategies might allow stopping the domino-like damage to further organ systems and offer alternatives beyond the currently available strictly supportive therapeutic options.